Substance Abuse and the HIV Situation in Malaysia. - Singh, Darshan; Chawarski, Marek C; Schottenfeld, Richard; Vicknasingam, Balasingam (Journal of food and drug analysis, 2013)
Heroin continues to be the main drug used in Malaysia, while amphetamine-type stimulants (ATS) have been recently identified as a growing problem. A cumulative total of 300,241 drug users were detected between 1988 and 2006. It is also estimated that Malaysia has 170,000 injecting drug users. HIV prevalence among drug users in the country ranges from 25% to 45%. Currently, there are approximately 380 general medical practice offices that offer agonist maintenance treatments for approximately 10,000 patients. There are 27,756 active patients in 333 general medical practice offices and government-run methadone maintenance treatment (MMT) centers. The Needle Syringe Exchange Program (NSEP) reached out to 34,244 injection drug users (IDUs) in 2011. In the last 2 years (2011 and 2012) the number of detected drug addicts decreased from 11,194 to 9015. The arrests made by the police related to opiate and cannabis use increased from 41,363 to 63,466 between the years 2008 and 2010, but decreased since 2010. An almost four-fold increase in the number of ATS and ketamine users was detected from 2006 (21,653 users) 2012 (76,812). Between 2004 and 2010, the yearly seizures for heroin ranged between 156 to 270 kg. However, in 2010 and 2011, heroin seizures showed a significant increase of 445kg and 410.02 kg, respectively. There has been a seizure of between 600 to 1000kg of syabu yearly from 2009 to 2012. Similar to heroin, increased seizures for Yaba have also been observed over the last 2 years. A significant increase has also been recorded for the seizures of ecstasy pills from 2011 (47,761 pills) to 2012 (634,573 pills). The cumulative number of reported HIV infections since 1986 is 94,841. In 2011, sexual activity superseded injection drug use as the main transmission factor for the epidemic. HIV in the country mainly involves males, as they constitute 90% of cumulative HIV cases and a majority of those individuals are IDUs. However, HIV infection trends are shifting from males to females. There are 37,306 people living with HIV (PLHIV) who are eligible for treatment, and 14,002 PLHIV were receiving antiretroviral treatment (ART) in 2011. The decreasing trend of heroin users who have been detected and arrested could be due to the introduction of medical treatments and harm reduction approaches for drug users, resulting in fewer drug users being arrested. However, we are unable to say with certainty why there has been an increase in heroin seizures in the country. There has been an increasing trend in both ATS users and seizures. A new trend of co-occurring opiate dependence and ATS underscores the need to develop and implement effective treatments for ATS, co-occurring opiate and ATS, and polysubstance abuse disorders. The low numbers of NSEP clients being tested for HIV underscores our caution in interpreting the decline of HIV infections among drug users and the importance of focusing on providing education, prevention, treatment, and outreach to those who are not in treatment.